Perfil social, recrutamento e trajetórias políticas :uma análise dos representantes do legislativo estadual capixaba, 1986-2010 - Pratti, Luana Puppin (2013)
The aim of this research is identify the socioeconomic profile of the parliamentarians from the state of Espirito Santo and observes their political trajectory patterns. Biographical data from the states Representatives were collected in order to verify social and economical characteristics, as well as their elective and administrative experiences. The analyzed hypothesis shows that specific qualities provide greater opportunities for leadership positions inside the Legislative Assembly of Espirito Santo ( Ales). The analyzed period covers the 11ª, 12ª, 13ª, 14ª, 15ª, 16ª and 17ª legislatures which correspond to the period between 1987- 2010. For the research development, it was necessary search for theorical basis on the assumptions of the theory of elites, the institutionalization theory, theory of ambition and political professionalization theory. It was also collected some analyses about social composition and political trajectories from the Brazilians legislatives to a better understanding of the dynamics of parliamentarians elite. It was possible to map a social and political profile from the members of Ales and relate their political trajectories with a position inside of the institution. As a result, it was confirmed that the personal characteristics have a huge importance for the construction of the political careers.